The protein phosphatase 2A catalytic subunit StPP2Ac2b enhances susceptibility to Phytophthora infestans and senescence in potato - Muñiz García, María Noelia (2022)
The serine/threonine protein phosphatases type 2A (PP2A) are involved in several physiological responses in plants, playing important roles in developmental programs, stress responses and hormone signaling. Six PP2A catalytic subunits (StPP2Ac) were identified in cultivated potato. Transgenic potato plants constitutively overexpressing the catalytic subunit StPP2Ac2b (StPP2Ac2b-OE) were developed to determine its physiological roles. The response of StPP2Ac2b-OE plants to the oomycete Phytophthora infestans, the causal agent of late blight, was evaluated. We found that overexpression of StPP2Ac2b enhancessusceptibility to the pathogen. Further bioinformatics, biochemical, and molecular analyses revealed that StPP2Ac2b positively regulates developmental and pathogen-induced senescence, and that P. infestans infection promotes senescence, most likely through induction of StPP2Ac2b expression.